Examining the Strategies and Outcomes of the Technological Competencies of Arabic Language Teachers in Schools of Babylon Province - Al-Jiryawee, Husam Abdulkadhim Rabeh; Hosseinpour, Mohammad; Al-Zuwaini, Ibtisam Sahib Mussa; Ghashghaeizadeh, Nasrolah (Assessment and Practice in Educational Sciences, 2026)
This study aimed to identify and analyze the strategies and outcomes associated with the development of technological competencies among Arabic language teachers in schools of Babylon Province. The study adopted a qualitative research design using the systematic grounded theory approach of Strauss and Corbin. The study population consisted of educational and technological experts, including university faculty members, policymakers, curriculum specialists, and experienced Arabic language teachers with a minimum of ten years of professional experience. Participants were selected through snowball sampling, and data collection continued until theoretical saturation was achieved. Data were gathered through 15 in-depth semi-structured interviews lasting between 20 and 60 minutes. Concurrent data collection and analysis were conducted using a three-stage coding process, including open coding, axial coding, and selective coding. To ensure the reliability of the qualitative analysis, the Holsti coefficient was calculated, yielding an acceptable reliability value. The extracted concepts and categories were organized into a paradigmatic model encompassing causal conditions, contextual conditions, intervening conditions, strategies, and outcomes. The findings revealed that the development of technological competencies among Arabic language teachers is a multidimensional and systemic process centered on a core phenomenon shaped by ten key categories. Causal conditions included the provision of technological infrastructure and the strengthening of technical and professional capabilities. Contextual conditions encompassed supportive governmental policies, school leadership, and a culture of technology acceptance. Intervening conditions such as continuity of professional development and professional networking played a mediating role. Strategic actions focused on innovation in Arabic language teaching and technology-oriented teacher empowerment, leading to outcomes including improved instructional quality, enhanced teacher competencies, increased student engagement, and sustainable professional development. The study concludes that effective development of technological competencies among Arabic language teachers requires an integrated and systemic approach that aligns infrastructure, policy support, professional learning, and pedagogical innovation to achieve sustainable educational improvement.